Opposing effects of actin signaling and LFA-1 on establishing the affinity threshold for inducing effector T-cell responses in mice - Palmer, Ed; Drobek, Ales; Stepanek, Ondrej (European journal of immunology, 2016)
Mature CD8(+) T cells use a narrow antigen affinity threshold to generate tissue-infiltrating cytotoxic effector T cells and induce autoimmune pathology, but the mechanisms that establish this antigen affinity threshold are poorly understood. Only antigens with affinities above the threshold induce stable contacts with APCs, polarization of a T cell, and asymmetric T-cell division. Previously published data indicate that LFA-1 inside-out signaling might be involved in establishing the antigen affinity threshold. Here, we show that subthreshold antigens weakly activate all major distal TCR signaling pathways. Low-affinity antigens are more dependent on LFA-1 than suprathreshold antigens. Moreover, augmenting the inside-out signaling by hyperactive Rap1 does not increase responses to the subthreshold antigens. Thus, LFA-1 signaling does not contribute to the affinity-based antigen discrimination. However, we found that subthreshold antigens do not induce actin rearrangement toward an APC, mediated by Rho-family GTPases, Cdc42, and Rac. Our data suggest that Rac and Cdc42 contribute to the establishment of the antigen affinity threshold in CD8(+) T cells by enhancing responses to high-affinity antigens, or by reducing the responses to low-affinity antigens.
Keywords: signální transdukce; receptory antigenů T-buněk; Cell Adhesion; Actins; Actin cytoskeleton; myši transgenní; LFA-1; T-cell receptor signaling; Receptors, Antigen, T-Cell; myši inbrední C57BL; Signal Transduction; aktiny; Mice; Rap1; antigen-1 spojený s lymfocytární funkcí; CD8-pozitivní T-lymfocyty; aktivace lymfocytů; Antigen affinity threshold; zvířata; Lymphocyte Activation; Lymphocyte Function-Associated Antigen-1; myši; buněčná adheze; CD8-Positive T-Lymphocytes; Mice, Transgenic; Mice, Inbred C57BL; Rho-family GTPases; Animals